THE ROLE OF MOTIVATION IN SECOND LANGUAGE ACQUISITION - Karimberganova Shahnoza Muxammad qizi; Ruzmetova Diana Kamilovna (Ta’lim innovatsiyasi va integratsiyasi, 2025)
Abstract Motivation is considered one of the most salient psychological constituents that significantly affect second language acquisition. Indeed, motivation significantly determines the extent of involvement, effort, and tenacity that learners must exhibit in the language learning process. Moreover, the abstract touches upon the roles of different internal and external factors that play a pivotal role in shaping motivation, such as the attitude of learners, learning environments, instructors, their cultural experiences, as well as their own goals. Recent studies show that learners with strong motivation usually demonstrate greater language competence in reading, writing, listening, as well as speaking skills, as this component significantly affects the practice carried out by learners. This study accentuates that motivation remains a dynamic component that keeps on fluctuating, and instructors must use different motivational techniques in order to establish positive environments.